Teachers’ Roles in Managing Buying–Selling Role Play to Foster Entrepreneurial Attitudes in Early Childhood Education - Hidayati, Zahra Aulia; Sianturi, Risbon; Aidilia Shaqi, Reva; Nuraida, Niken (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to describe the role of teachers in managing buying–selling role-play activities as a medium for developing entrepreneurial attitudes in children aged 4–6 years at Sejahtera 4 Kindergarten. The study focused on teacher planning, management of activity implementation, and the forms of entrepreneurial attitudes that emerged during children’s participation in the role play. This research employed a descriptive qualitative approach involving one classroom teacher as the main subject, with data collected through in-depth interviews and light observation of teachers’ explanations and activity arrangements. The findings indicate that teachers play a strategic role in designing learning activities by setting objectives, preparing play scenarios, and providing supporting media such as tables, merchandise, and toy money. Through scaffolding and guided assistance, teachers facilitated children’s initiative, communication, negotiation, decision-making, and simple problem-solving skills during the buying–selling simulation. Previous studies have largely emphasized the social-emotional benefits of role play, while limited attention has been given to teachers’ managerial roles in fostering entrepreneurial attitudes in early childhood. This study contributes theoretically by extending the discussion of entrepreneurship education within a play-based learning framework and practically by offering insights for teachers to design structured role-play activities that more intentionally support entrepreneurial character development in early childhood settings